Students' Translation Use in English Foreign Language (EFL) Learning - Siregar, Masitowani (Association of Language Teachers in Southeast Asia (ALTSA), 2020)
The study was conducted to describe the studentsÃ¢â‚¬â„¢ translation use in English Foreign Language Learning (EFL). The subject of the study was 100 students English Educational Study Program Languages and Arts Faculty, Universitas Negeri Medan. 40 Students were selected as the sample. The instruments used to collect data were questionnaire and interview. The data analysis indicated that English Department Students as foreign language learners used translation activities during their learning process such as, to comprehend reading text, to write English texts, to speak English, to understand vocabularies, to understand English grammar, to understand idioms and phrases and to understand the instructions of teachers.Ã‚Â More attention should be given than to help the studentsÃ¢â‚¬â„¢ skills and understanding through the translation process.